Analisis Risiko Kecelakaan Kerja Pada Pembangunan Konstruksi Tower Besi Baja SUTET - Alfandi Arifuddin; M. Natisr Abduh; Hijriah Hijriah (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The implementation of construction activities has the potential to cause hazards or risks that can cause losses that can be said to be a lot in terms of time, material, and cost. At each work location there is a risk of work accidents that can interfere with work activities in a work activity. Things that cause work accidents are the lack of knowledge of good Occupational Safety and Health (K3) and also the lack of implementation of the Occupational Health and Safety Management System (SMK3). Transmission tower construction work is part of infrastructure work that has a fairly high level of risk in the construction world due to the lack of awareness of the workforce to use PPE and are free from aspects of work machines and equipment. This study intends to understand the OHS risk and measure the level of risk. The type of research is quantitative research with the method used in risk assessment in this study is AS/NZS4360. The data was obtained from a questionnaire technique distributed to respondents, while the intended respondents were contractors who had knowledge of K3. From the results of the study, it was found that the most potential risk of falling objects occurred with a percentage of 32% and the potential risk of falling workers had the highest potential risk (High Risk).